EVALUACIÓN DEL EFECTO DE TRES NIVELES DE FITASA EN POLLOS BROILERS, EN LA FASE DE CRECIMIENTO Y ACABADO EN EL CANTÓN BABAHOYO - SÁNCHEZ LUCAS, ADRIÁN JOSUÉ (2018)
SUMMARY. With the objective of evaluating three levels of phytase in the growth and finishing stages of broiler chickens, experimental work is carried out at the San Pablo Farm of the Faculty of Agricultural Sciences of the Technical University of Babahoyo. The objective of the trial was to evaluate the productive parameters and the benefit-cost analysis using phytase with a commercial balance of low nutritional quality. The trial was evaluated through the Completely Random Design under Tuckey's 5% comparison. Five repetitions were used for each treatment, the same ones that responded to the doses of phytase 0 gr / tn, 400 gr / tn and 800 gr / tn of food, the experimental unit being constituted by 12 chicks that were of the Cobb 500 line. The duration of the trial was six weeks in which data were recorded on food consumption, weight gain, feed conversion, mortality and benefit-cost analysis. A greater consumption of food could be observed in the treatments 800 gr / tn and 400 gr / tn of phytase in food, weights greater than 2755.00 gr and 2599.80 gr respectively. As well as some final conversions of 1.46 and 1.52. The benefit-cost analysis of the best result was for the treatment 800 gr / tn, this being 2,870. Therefore, the best treatment in this test is the commercial phytase balanced at a rate of 800 gr / tn of food. Keywords: phytase, food, assay, productive parameters, treatments.